Protests in Hong Kong : roots in old and new social movements - Wu, Feng Shi (2015)
The eleven-day standoff in Hong Kong city central is not a single-issue triggered mass event. It is a result of two strands of social mobilisation: the pro-democracy movement with a history of over three decades, and the recent and increasingly radicalised youth activism.